THE ROLE OF AMYLOID BETA PLAQUES AND TAU TANGLES IN THE PROGRESSION OF ALZHEIMER’S DISEASE - Shinjini Biswas (International Educational Journal of Science and Engineering, 2025)
Alzheimer’s disease is a progressive, currently irreversible brain disorder that destroys memory and thinking skills and is widely recognized as the most common category of dementia, a specific group of symptoms that affect memory, problem-solving, language, and behavior that can widely interfere with both daily life and standards of living. Alzheimer’s disease is a disease that is primarily caused by a buildup of both amyloid and tau proteins in the brain. These proteins form plaques and tangles that block communication between nerve cells, which leads to their death. In addition, in terms of the manner in which Alzheimer’s disease functions, Alzheimer’s can be categorized as a progressive disease, through which symptoms start mild and gradually worsen over time. As of the present day, there is no cure for Alzheimer’s disease, but medications and management strategies can temporarily improve symptoms. Out of all the factors that can widely affect the progression of Alzheimer’s disease, such as genetics, vascular health, lifestyle, and age, something that can largely contribute to the overall development of the disease is none other than amyloid beta plaques and tau tangles.